Potential of Organic Farming in Production of Environment Friendly Sugarcane - Kumari, Reeta; Nautiyal, Aparna; Dhaka, Neeti; Deepali; Bhatnagar, Sonal (Current Nutrition & Food Science, 2014)
Sugarcane draws heavily from soil and requires corresponding replenishment of nutrients. With the increasingly crop residue and farm waste, finding alternative uses for supplementing the soil has become more acute. Long-term use of inorganic fertilizers and pesticides to enhance the productivity of sugarcane results in deterioration of soil quality and the decline in productivity. It also contributes to the accumulation of heavy metals in soil and raising concern about crop production and potential impact on human health. Stubble decline, characterized by progressive reductions of yield in successive crops, is a major constraint on productivity and profitability of the sugarcane industry due to poor soil aeration, drainage, weed competition and Pythium root rot. To facilitate sugarcane cultivation on a sustainable basis, and at the same time obtain product more acceptable in international market, it is advisable to apply biofertilizers and promote organic farming. Application of different biofertilizers such as Azotobacter, Pseudomonas, Azospirillum, Trichoderma, Gliocladium sp. AM fungi (Glomus fasciculatum, Glomus intraradices and Gigaspora albida) and Seaweeds (Caulerpa racemosa, Ulva lactuca, Sargassum wightii, Gelidiella acerosa and Gracilaria edulis), has shown significant improvement in sugarcane yield. Biofertilizers improve soil physical properties, such as porosity, aeration and water infiltration by forming and stabilizing soil aggregates. Composted organic materials have been utilized with varying success for suppression of root rot in sugarcane that would result in increased production and productivity. Studies have also indicated that it is feasible to make a comparable yield of sugarcane by meeting the nutrient demand entirely through organics. The farm produce will not contain traces of hazardous substances and will be accepted across the globe as a premium organic product.
Keywords: soil fertility